Preoperative N-terminal pro-B-type natriuretic peptide and myocardial injury after stopping or continuing renin–angiotensin system inhibitors in noncardiac surgery: a prespecified analysis of a phase 2 randomised controlled multicentre trial - Gutierrez del Arroyo, Ana; Patel, Akshaykumar; Abbott, Tom E.F.; Begum, Salma; Dias, Priyanthi; Somanath, Sameer; Middleditch, Alexander; Cleland, Stuart; Brealey, David; Pearse, Rupert M.; Ackland, Gareth L.; Ackland, Gareth; et al. (British journal of anaesthesia : BJA, 2024)
Patients with elevated preoperative plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP >100 pg ml−1) experience more complications after noncardiac surgery. Individuals prescribed renin–angiotensin system (RAS) inhibitors for cardiometabolic disease are at particular risk of perioperative myocardial injury and complications. We hypothesised that stopping RAS inhibitors before surgery increases the risk of perioperative myocardial injury, depending on preoperative risk stratified by plasma NT-proBNP concentrations. In a preplanned analysis of a phase 2a trial in six UK centres, patients ≥60 yr old undergoing elective noncardiac surgery were randomly assigned either to stop or continue RAS inhibitors before surgery. The pharmacokinetic profile of individual RAS inhibitors determined for how long they were stopped before surgery. The primary outcome, masked to investigators, clinicians, and patients, was myocardial injury (plasma high-sensitivity troponin-T ≥15 ng L−1 or a ≥5 ng L−1 increase, when preoperative high-sensitivity troponin-T ≥15 ng L−1) within 48 h after surgery. The co-exposures of interest were preoperative plasma NT-proBNP (< or >100 pg ml −1) and stopping or continuing RAS inhibitors. Of 241 participants, 101 (41.9%; mean age 71 [7] yr; 48% females) had preoperative NT-proBNP >100 pg ml −1 (median 339 [160–833] pg ml−1), of whom 9/101 (8.9%) had a formal diagnosis of cardiac failure. Myocardial injury occurred in 63/101 (62.4%) subjects with NT-proBNP >100 pg ml−1, compared with 45/140 (32.1%) subjects with NT-proBNP <100 pg ml −1 {odds ratio (OR) 3.50 (95% confidence interval [CI] 2.05–5.99); P<0.0001}. For subjects with preoperative NT-proBNP <100 pg ml−1, 30/75 (40%) who stopped RAS inhibitors had myocardial injury, compared with 15/65 (23.1%) who continued RAS inhibitors (OR for stopping 2.22 [95% CI 1.06–4.65]; P=0.03). For preoperative NT-proBNP >100 pg ml−1, myocardial injury rates were similar regardless of stopping (62.2%) or continuing (62.5%) RAS inhibitors (OR for stopping 0.98 [95% CI 0.44–2.22]). Stopping renin-angiotensin system inhibitors in lower-risk patients (preoperative NT-proBNP <100 pg ml −1) increased the likelihood of myocardial injury before noncardiac surgery.